Reconstruction of Marine Commercial Landings for the Brazilian Industrial and Artisanal Fisheries From 1950 to 2015 - Freire, Kátia Meirelles Felizola; Almeida, Zafira da Silva de; Amador, José Raimundo Emanoel Trindade; Aragão, José Augusto; Araújo, Ana Rosa da Rocha; Ávila-da-Silva, Antônio Olinto; Bentes, Bianca; Carneiro, Marcus Henrique; Chiquieri, Julien; Fernandes, Cezar Augusto Freire; Figueiredo, Marina Bezerra; Hostim-Silva, Maurício; et al. (Frontiers in Marine Science, 2021)
Landing data are the most basic information used to manage fisheries, although they are often unavailable or incomplete. The objective of this work was to reconstruct the national database of marine commercial landings for the Brazilian industrial and artisanal fisheries, from 1950 to 2015. Total landings increased strongly from 1950 to mid-1980s and suffered sharp decline in the early 1990s, mainly associated to the collapse of sardine fisheries. After that, another period of increasing landings was observed, but at a much lower rate. Industrial landings always surpassed artisanal landings in Brazilian waters, except for the beginning of the time series, when many industrial fleets had not started yet, and in the early 2000s, when a change in the methodology for collecting landing statistics was implemented in the state of Pará leading to an overestimation of artisanal landings. Artisanal fisheries have been declining since 2005, which is worrisome due to the social impact. Regional differences were also observed, with industrial landings being always higher than artisanal landings in southeastern-southern Brazil, while the opposite was true for the northern-northeastern regions. Higher landings were observed in the southeastern-southern regions when both artisanal and industrial fleets were combined. Sardine and demersal fishes were the main resources landed by industrial fishers. Artisanal fishers caught more species than their industrial counterpart, featuring Xiphopenaeus kroyeri, Cynoscion acoupa, and Ucides cordatus. Although the fishing of Epinephelus itajara was banned in Brazil, it continues to be landed. Yet, catches of this species and others under some threat status are still not properly registered, including: Carcharhinus longimanus, Galeorhinus galeus, Sphyrna lewini, Sphyrna mokarran, Pristis pectinata, and Pseudobatos horkelii. Fishing resources not identified in previous landing reconstruction efforts, such as sea urchins and sea cucumbers, have now been reported. The database presented here should be continuously updated and improved. It is of paramount importance to resume the collection of landing statistics, including information on fishing effort, to assess the relative impact of fisheries and environmental factors on the main Brazilian fishing stocks.